Uniportal video-assisted thoracoscopic lobectomies in lung cancer management - A. I. Arsen’Ev; A. O. Nefedov; A. A. Barchuk; S. A. Tarkov; K. A. Kostitsyn; A. V. Nefedova (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The study summarized personal surgical experience of uniportal video-assisted thoracoscopic (VATS) lobectomies for patients with stage I-II non-small cell lung cancer. MATERIAL AND METHODS. The authors have performed 72 VATS lobectomies for patients with stage I-II non-small lung cancer using modified minimally invasive single incision above anterior part of musculus latissimus dorsi. RESULTS. During the implementation period, there were carried out 2 (2,8 %) conversions to open thoracotomy. There weren’t observed lethal postoperative complications of VATS lobectomies. Other complications had 5 (6,9 %) patients. Postoperative pneumonia was in 1 (1,4 %) patient. Arrhytmia was noted in 4 (5,6 %) patients. The average operation time consisted of 227,4 min (from 60 to 460 min). Learning curve demonstrated a significant decrease of operation time with every following VATS lobectomy from 227,4 to 90,3 min (p=0,03). The quantity of removed regional lymph nodes estimated 14,2 ± 0,7 during uniportal VATS lobectomy. The median blood loss was 98,3 ml (from 10 to 300 ml). The average duration of air leak was 2,3 ± 0,65 days after uniportal VATS lobectomy. The mean term of drainage was 4,6 ± 0,53 days. CONCLUSIONS. The data obtained justified the feasibility, efficacy and safety of VATS lobectomies in patients with I-II stage of lung cancer.